ANALISIS PERAN PEMANGKU KEPENTINGAN DALAM PENGEMBANGAN SMART CITY DI KABUPATEN SOLOK SELATAN - Muhammad Ilham Nur Ikhsan Rintaka (Halu Oleo University, 2025)
This study focuses on the implementation of the smart city concept in South Solok Regency, which is part of the 100 Smart City program in Indonesia. Using the stakeholder analysis concept proposed by Ackermann & Eden (2011) and the penta-helix model by Vani et al. (2020; Yesayabela et al., 2024), this research aims to reveal strategies for adapting the smart city concept in small cities in developing countries. This study employs a qualitative method, with data collected through Focus Group Discussions (FGD) and in-depth interviews with key stakeholders, namely local government, industry players, academics, and community members. The results show that the government plays a key role as the policy maker and facilitator, while the private sector provides technological infrastructure. Academics contribute research-based data to support decision-making, though their contributions are still limited. The community actively participates as end users and beneficiaries. The mass media serve as an important tool to spread information and raise public awareness. The study concludes that the success of implementing the Smart City concept in South Solok depends heavily on the synergistic collaboration among the government, private sector, academics, the community, and the mass media. The local government, as the main player, needs to optimise its role as a policymaker to ensure that all elements can contribute optimally to the development of the smart city.